PENGARUH FRAUD PENTAGON TERHADAP KECURANGAN LAPORAN KEUANGAN - Theressa Meita Natalia; Luhgiatno Luhgiatno; Mohklas Mohklas (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2021)
This study aims to determine the effect of pentagon fraud on fraudulent financial reporting. Pentagon fraud is proxied by five variables, namely the pressure factor which is proxied by external pressure, the opportunity factor is proxied by the ineffective monitoring, the rationalization factor is proxied by the audit opinion, the competence factor is proxied by the change of directors and the arrogance factor is proxied by the dualism of positions which are hypothesized to affect the fraudulent financial reporting. Population in this study were property and real estate companies listed on the Indonesia Stock Exchange for the period 2016-2019. There are 36 company data with the number of observations for 4 years (2016-2019) as many as 144 research samples obtained by purposive sampling method. Methods of data analysis using the SPSS 26 program. Results of this study indicate that external pressures have a negative and significant effect on fraudulent financial reporting. Meanwhile, ineffective monitoring, audit opinion, change of directors and dualism of positions did not have a significant effect on fraudulent financial reporting.